(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
Accounting and auditing are essential pillars of effective business management, providing the foundation for accurate financial reporting, decision-making, and organizational accountability. Accounting involves the systematic process of recording, classifying, and summarizing financial transactions to generate meaningful financial information. This information helps managers, investors, creditors, and other stakeholders understand the financial health and performance of a business. Auditing complements accounting by offering an independent and objective assessment of a company’s financial statements, ensuring their accuracy, completeness, and compliance with established accounting standards and regulations.